Heterogeneous activation of peroxymonosulfate by stable Co-MOF for the efficient degradation of organic dye pollutants. Issue 38 (15th September 2022) - Xie, Wei; Yuan, Yuan; Jiang, Wei; Zhang, Shu-Ran; Xu, Guang-Juan; Xu, Yan-Hong; Su, Zhong-Min
Abstract : A new Co-MOF with splendid stability can act as an excellent heterogeneous catalyst to activate peroxymonosulfate, exhibiting highly efficient organic dye degradation in aquatic environments. Abstract : A novel cobalt-based metal–organic framework (Co-MOF), [Co(PBA)(pic)(H2 O)]·H2 O·0.5DMA ( N, N -dimethylacetamide (DMA), 2-picolinic acid (Hpic), and 4-(pyridin-4-yl)benzoic acid (HPBA)) was synthesized by a facile solvothermal method. Co-MOF possesses good stability in aqueous environments. Co-MOF can be used as an outstanding heterogeneous catalyst to degrade methyl orange (MO) dye with high performance via peroxymonosulfate (PMS) activation. The degradation efficiency of MO was above 98% within 4.5 min under 20 mg L −1 organic pollutant dosage, and the rate constant of the Co-MOF/PMS system is approximately 14 times higher than that of PMS only. Moreover, the influencing factors of MO concentration, catalyst dosage, PMS dosage and reaction temperature were evaluated. The radical trapping reaction confirmed that sulfate (SO4 ˙ − ) and hydroxyl (˙OH) radicals were the dominant radicals, and the possible degradation mechanism of MO was thus proposed. Besides, the Co-MOF catalyst possesses reusability for MO dye removal via PMS activation in aqueous environments. This study offers insight into building stable MOF heterogeneous catalysts for high-efficiency PMS activation for environmental remediation.